ANALISIS USAHA TERNAK AYAM BROILER KEMITRAAN DI KABUPATEN KARANGANYAR - Himmah Nur Hayati; Minar Ferichani; Isti Khomah (Universitas Sebelas Maret, 2019)
This research is aimed to analyze cost, revenue, profit, profitability, Break Event Point, business efficiency and the risks of broiler chicken farming in Jumantono District, Karanganyar Regency. This research was conducted in June-July 2018. Data used was one production period (35 days). The basic method in this study is descriptive analytical method and using case study techniques. Determination of the location of the study was carried out by purposive (intentional), namely in the District of Jumantono, Karanganyar Regency. The respondents were taken by quota sampling method as many as 30 respondents. The types and and sources of data consist of primary data and secondary data. Data collection techniques are carried out by interview, observation and recording. The results showed that the average total cost of broiler chicken farming was IDR 124,291,091 and the average income was IDR 165,114,558, - so that the profits obtained were IDR 40,823,467. Broiler chicken farms in Jumantono District, Karanganyar Regency benefit from a profitability rate of 32.85%. Nliai R / C ratio or broiler chicken business efficiency of 1.32. BEP products from broiler chicken farms amounted to 1,665.1 kg, BEP sales amounted to IDR 29,391,635, and BEP prices were IDR 13,489 / kg. Broiler chicken farming in Jumantono District, Karanganyar Regency has a CV value of ≤ 0.5 or L ≥ 0 so that it avoids the risk, because the lower limit of profit (L) shows a positive value (+).